A tale of two algorithms: The appeal and repeal of calculated grades systems in England and Ireland in 2020 - Kelly, Anthony (British educational research journal, 2021)
The Covid pandemic and the cancellation of state examinations caused unprecedented turmoil in the education systems on both sides of the Irish Sea. As the policy of calculating grades using purpose‐built algorithms came undone in the face of a barrage of appeal, protest and legal action, the context in which the policies had been devised collapsed. The British and Irish governments had initially adopted similar approaches to issuing examination grades, but then diverged into different stratagems pre‐ and post‐results, with significantly different outcomes. The Irish examination system emerged relatively unscathed, while the system in England suffered what was probably its greatest policy failure of modern times. This article examines and memorialises how and why this happened, and draws lessons for a future in which school closures and substitute examinations become the ‘new normal’.